Sources of laminated sediments in the northeastern Arabian Sea off Pakistan and implications for sediment transport mechanisms during the late Holocene. (January 2019) - Forke, Sven; Rixen, Tim; Burdanowitz, Nicole; Lückge, Andreas; Ramaswamy, Venkitasubramani; Munz, Philipp; Wilhelms-Dick, Dorothee; Vogt, Christoph; Kasten, Sabine; Gaye, Birgit
Laminated sediments of the continental slope off the Makran coast in the northern Arabian Sea are well-known climate archives and record productivity, as well as supply of material from land. Here, we studied sediment core 275KL off Pakistan in concert with sediment trap, dust and river samples in order to characterize and quantify land-derived material deposited in varves and event layers. We analysed grain sizes, mineral assemblages, bulk components and stable isotopes (δ 13 C, δ 18 O) of carbonates. In winter, enhanced river discharge is the main source of lithogenic matter contributing the major amounts to the total annual sedimentation of the northern Arabian Sea. During the late summer season, lithogenic matter accumulation is slightly enhanced, probably carried along with the south-eastward blowing Levar winds from the Balochistan and the Sistan Basins and the summer monsoon discharge maximum of perennial streams. C/N ratios and stable carbon and oxygen isotopes could not be used to distinguish between organic matter produced on land and in the ocean, whereas stable carbon and oxygen isotope ratios of carbonates suggest that sedimentation of event layers is dominated by direct inputs from land. Catastrophic denudation and storm events occur on average once every 50 years and lead to sedimentation rates that exceed the mean annual sedimentations of 983 g m −2 yr −1 by 6 to 10 times. Nevertheless, due to their rare occurrence, they contributed only 7% to the total sedimentation during the last ca. 5000 years. End-member modelling of grain sizes in accordance with lithogenic matter accumulation rates and event layer frequencies showed that arid conditions prevailed between 4000 and 5000 a BP while more humid conditions commenced around 2000 ka BP in accordance with the Pacific ENSO record.